(untitled) (Advancements in Homeopathic Research, 2024)
This 21st century act as a double –edged sword on the modern civilization. In this era, a group of people are in rat race competition. This brings mental stress and strain which causes developmental of gastrointestinal disease. Irritable bowel syndrome is multifactorial disorder of GIT tract causing disturbances in gastric motility, resulting in abdominal pain and altered bowel habits. A changing lifestyle and modernization imply a change in eating habits, decreased sleep and increase in stressful competitive atmosphere. These factors contribute to large number of psychosomatic disorders. IBS is a common cause of referral and accounts for frequent absenteeism from work and impaired quality of life.